Balancing Performance and Confidentiality in Air Index - TAN, Qingzhao (Institutional Knowledge at Singapore Management University, 2005)
Studies on the performance issues (i.e., access latency and energy conservation) of wireless data broadcast have appeared in the literature. However, the important security issues have not been well addressed. This paper investigates the tradeoff between performance and security of signature-based air index schemes in wireless data broadcast. From the performance perspective, keeping low false drop probability helps clients retrieve the information from a broadcast channel efficiently. Meanwhile, from the security perspective, achieving high false guess probability prevents the hacker from guessing the information easily. There is a tradeoff between these two aspects. An administrator of the wireless broadcast system may balance this tradeoff by carefully configuring the signatures used in broadcast. This study provides a guidance for parameter settings of the signature schemes in order to meet the performance and security requirements. Experiments are performed to validate the analytical results and to obtain optimal signature configuration corresponding to different application criteria.